Breast milk as an etiological factor in infantile disorders – An observational study - Rajanish Meti (Elsevier, 2021)
Background: Charaka, Sushruta, and Kashyap Samhita mentions Stanya as Upa dhatu of Rasa and described the importance of Stanya (breast milk) as primary diet for growth and development of infants. As per Ayurveda Samhitas, dushita stanya (vitiated breast milk) is responsible for various morbidities. Objective: Validation of organoleptic methods to find out breast milk vitiation and to verify doshas in breast milk as an etiological factor in infantile disorders. Materials and methods: Hundred breast milk samples were collected from lactating mothers feeding their babies only breast milk, with babies’ in the age group of 1–6 months. Each sample was examined by organoleptic methods (Avaseedati, Tantuvat, Rajyoambhasi, Picchilam, Ghanam, Dravam, etc.) and laboratory investigations (pH, specific gravity, viscosity, and fat content). Result: All breast milk samples were found to have varying dosha vitiated characters. Amongst them Tridosha Dushti and characters like Avaseedati, Plavate, and Rajyoambhasi were found more frequently. Among the infants, 19% did not have any type of dosha vitiation symptoms and 81% presented with various symptoms. Similarity in dosha between the symptoms of infants and vitiation of their mother's breast milk existed in 26% and 55% showed dissimilarity in doshas. Conclusion: The physical characteristics of the milk may be influenced by several factors like food habit, psychological status, nutritional status of mother, period of lactation and at least in 26% of cases of infantile disorders, vitiation of milk was found with symptoms in infants showing similar dosha vitiation characters.